Innovation Hot Spots: the Case of the Computer Services Sector in the Region of Attica, Greece - Ioannis Katsikis; Klas Eric Soderquist; Gregory Prastacos (European Regional Science Association (ERSA), 2006)
Elaborating on the notion innovation hot spots, we examine the case of the computer services sector in the Region of Attica, Greece. Fast-growing, geographically and industrially clustered firms are becoming an increasingly important factor for innovation and regional development. As a result, innovation hot spots enjoy rapid growth, leading to job creation, knowledge expansion and, in the best cases, sustainable development. The most recent European Trend Chart Reports (2004 and 2005) present Greece as innovation leader in the computer services sector. Computer services are characterized by a high knowledge creation and knowledge diffusion intensity meaning that the hot spots exploiting such services position high on an innovation intensity scale. Consulting, implementation, operations management and support services enjoy similar growth since they are complementary industries forming the Attica IT innovation hot spot. The purpose of our research within this field is twofold. First, we present the conditions under which this innovation leadership has emerged and come to flourish. We argue that growth in the Region of Attica has been boosted by the Information Society Program, the Olympic Games and the necessity for modernizing Greek firms, which leads them to favor investments in new technologies. Moreover, the region presents a favorable macroeconomic environment, characterized by high rates of development, increase of consumption and investments. Second, we analyze and propose a framework for maintaining the dynamics in the region -and in innovation hot spots in general- as there is a significant risk of rise-and-fall patterns occurring, leading to former hot spots transforming into "blind spots", and core competencies developed turning into core rigidities and cultural lock-in.
Keywords: 330